Penggunaan Bungkil Inti Sawit Fermentasi oleh Jamur Pleurotus ostreatus dalam Ransum terhadap Performans Ayam Broiler - Noferdiman, Noferdiman (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The experiment was aimed to determine the effect of  Palm Kernel Cake fermentation by Pleurotus ostreatus  (BISF)  in  ration  on  the  performance  of  broiler  chicken.  The  experiment  was  assigned  into Completely Randomized Design (CRD) with  4  treatments and 5 replications. The  treatments were level of BISF  into the ration (P0 : 0%, P1 : 10 %, P2 : 20 %,  and P3 : 30 %). The observed variables were the feed consumption, body weight gain, feed conversion ration, carcass percentage, and the percentage of abdominal fat. The result of this study  showed that  added BISF were   significantly (P<0.01) feed  consumption, body weight gain, feed conversion ration, carcass percentage, and the percentage of abdominal fat. The experiment showed the that fermentation of Palm Kernel Cake (BISF) could be fed to the broiler chicken up to 20 %.